Adenovirus Manipulation for Use as an Effective Delivery Vector - O'Riain, Aidan (Trinity Student Medical Journal, 2022)
Adenoviruses are used as delivery vectors in many different biotherapeutic systems to provide treatment options in several clinical settings. Their relative safety, potent induction of an immune response, and ease of production have allowed these vectors to appear at the forefront of clinical medicine in recent times, with applications in gene therapies, cancer treatments, and vaccines (including those for SARS-CoV-2). Their ease of genome manipulation and large gene transduction abilities make them particularly attractive for use as delivery vectors. This paper aims to show that, despite significant challenges, adenoviruses have generally been effective as delivery vectors for gene therapies and vaccination strategies. Taking advantage of their diversity and delineated viral tropism is critical to implementing effective clinical strategies, moderating the negative effects of pre-existing immunity, combatting transient action, and optimising target cell specificity. Overall, this paper argues that adenoviral vectors are a promising tool for use in a wide range of clinical applications.